The contribution of BTK signaling in myeloid cells to neuroinflammation - Bassani, Claudia; Molinari, Marta; Romeo, Valentina; Martinelli, Vittorio; Boschert, Ursula; Martino, Gianvito; Muzio, Luca; Farina, Cinthia (Frontiers in Immunology, 2025)
IntroductionBruton’s tyrosine kinase (BTK) is a member of the TEC family of non-receptor tyrosine kinases expressed in cells of hematopoietic origin, including B lymphocytes and myeloid cells. Selective BTK inhibitors (BTKi) have shown efficacy in clinical trials in multiple sclerosis (MS). Here we investigated the role of BTK in human and mouse myeloid cells in in vitro and in vivo studies.MethodsWe evaluated i) the impact of the BTK inhibitor (BTKi) evobrutinib on monocyte markers for activation, costimulation, adhesion and phagocytosis in peripheral blood mononuclear cell (PBMC) cultures from healthy and MS subjects; ii) the therapeutic effects and the action of evobrutinib on myeloid cell phenotype in the experimental autoimmune encephalomyelitis (EAE) model of MS; iii) the contribution of BTK in short-lived vs. long-lived myeloid cells to EAE expression via experiments with double transgenic mice allowing inducible inactivation of BTK in CX3CR1 expressing cells. ResultsWe report that BTKi supported monocyte expression of VLA4/CD49d, an integrin directing immune cell migration towards the central nervous system, and CD163, a well-known scavenger receptor involved in removal of myelin debris, in samples from healthy subjects. This effect was maintained under distinct inflammatory settings and replicated with PBMC of MS subjects. Therapeutic intervention with evobrutinib ameliorated EAE severity and was associated with a significant modest decrease in the frequency of CNS-infiltrating proinflammatory macrophages. However, conditional BTK deletion in short-lived or long-lived CX3CR1-positive cells did not reduce EAE severity. DiscussionThis functional evidence questions the real contribution of BTK expressing myeloid cells to experimental MS.